Efektivitas Ceramah Interaktif Dua Arah Terhadap Peningkatan Pengetahuan Ibu Hamil Dan Pendamping Ibu Hamil Tentang Pemberian Asi Eksklusif - Astrid Oktavia Mukti; Widya Ayu Kurnia Putri; Rizka Novia Chrisjayanti; Fishka Diah Betari; Asep Mulyana; Lina Nuruzzati; Indah Luzclarita; Ruwi Sri Handini (Jurnal Gizi dan Kuliner, 2021)
(The low coverage of exclusive breastfeeding is one of the nutritional problems in Indonesia. Several factors influence exclusive breastfeeding, including family support, mother's knowledge about breastfeeding, mother's motivation, and socio-culture. Two-way interactive lecture is a delivery of information and receiving information. This study aims to determine the effectiveness of providing nutrition education through the lecture method with two-way interactive communication to increase motivation, knowledge, myths, family support and attitudes of pregnant women and pregnant women's companions about exclusive breastfeeding. This study used a quasi-experimental design with a one-group pretest posttest design for pregnant women. With a two-way interactive lecture method using power point. The results showed an increase in motivation of 92%, an increase in the knowledge category by 65%, an increase in the myth category by 3%, an increase in the family support category by 13%, and an increase in the attitude category by 37%. There was an increase in participants' knowledge before and before the intervention. There was a significant difference between before and before presenting the intervention. Keywords: Pregnant women, Nutrition Education, exclusive breastfeeding